2013
DOI: 10.1002/ppul.22873
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in childhood allergic asthma management: A randomised controlled trial

Abstract: FeNO measurements in childhood asthma management did not improve the proportion of symptom-free days, but did result in fewer asthma exacerbations associated with an increased leukotriene receptor antagonist use and an augmentation of the inhaled corticosteroid doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 27 publications
3
73
0
Order By: Relevance
“…(44) FENO has been shown to correlate with health outcomes in asthma; in one study, the cohort monitored by FENO had an increased use of leukotrienes and inhaled corticosteroids and decreased exacerbation frequency compared with the control group. (45) FENO is promising for use as a potential endpoint for clinical studies of aerosol medications specifically for inflammatory lung disease, especially as reference equations have begun to be generated.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%
“…(44) FENO has been shown to correlate with health outcomes in asthma; in one study, the cohort monitored by FENO had an increased use of leukotrienes and inhaled corticosteroids and decreased exacerbation frequency compared with the control group. (45) FENO is promising for use as a potential endpoint for clinical studies of aerosol medications specifically for inflammatory lung disease, especially as reference equations have begun to be generated.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%
“…The baseline daily ICS dosage of 320 mg was near the plateau of doseresponse curve, allowing little room for improvement on the daily symptoms and lung function. 3 Add-on LTRA to ICS also offers little additional benefit on asthma control and FEV 1 . 4 On the other hand, it has been shown that enhanced adherence to ICS may result in elevation of the threshold of asthma exacerbation.…”
mentioning
confidence: 97%
“…1 The authors aimed to employ fractional exhaled nitric oxide (FeNO), a surrogate marker for eosinophilic airway inflammation, in guiding drug treatment for children with mild to severe persistent asthma. Patients were allocated into the clinical group or the FeNO group.…”
mentioning
confidence: 99%
“…FeNO testing has shown its value in identifying individuals who respond to inhaled corticosteroids [7][8] and biologic therapy [9] and has acted as a complement to conventional monitoring of asthma in children and adults in several randomized controlled clinical trials [10][11][12][13][14][15][16]. Moreover, in 2014, the National Institute for Health and Care Excellence (NICE) recommended FeNO testing to help diagnose asthma in adults and children when diagnosis is unclear.…”
Section: Introductionmentioning
confidence: 99%